The Effect of Hamstring Muscle Group Stretch On Muscle Flexibility And Quality Of Life In Osteoarthritis Patients - Fahmi, Faradisa Yuanita; Ellyana, Ellyana; Warsono, Warsono (Media Keperawatan Indonesia, 2023)
Osteoarthritis is the most common disease of arthritis which is defined as chronic inflammation of the joints due to damage to the cartilage. The global prevalence of knee osteoarthritis is 3.8% and 0.85% of hip osteoarthritis. Meanwhile in Indonesia, based on the results of the 2018 Riskades, it showed that the prevalence of joint disease was recorded at around 7.3%. The aim of this study was to determine the effect of stretching the hamstring muscle groups on muscle flexibility and quality of life in osteoarthritis patients at the Kaliwungu Health Center. This research uses the quasy experiment with pretest and posttest with control group design. Statistical test of the effect of stretching the hamstring muscle groups on muscle flexibility in the group obtained p = 0.00. Statistical test of hamstring muscle stretching on quality of life obtained a p value of 0.00. Stretching the hamstring muscle group is a therapy to lengthen muscles that experience shortening or decreased muscle elasticity and flexibility due to both pathological and physiological factors. Increased muscle tone can affect the patient's quality of life. There is an effect of stretching the hamstring muscles on muscle flexibility and quality of life in patients with osteoarthritis at the Kaliwungu Health Center.